On some generalized sequence spaces - Et, M; Altinok, H; Altin, Y (Elsevier Science Inc, 2004)
The idea of difference sequence spaces was introduced by Kizmaz [Canad. Math. Bull. 24 (1981) 169] and this concept was generalized by Et and Colak [Soochow J. Math. 21 (1995) 337]. In this paper we define the sequence spaces l(infinity)(p)(Delta(v)(r)), c(p)(Delta(v)(r)), c(0)(p)(Delta(v)(r)) and (c) over bar (p)(Delta(v)(r)), (r is an element of N), give some topological properties and inclusion relations of these sequence spaces. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: difference sequence spaces; statistical convergence